HUBUNGAN POWER OTOT TUNGKAI DAN KELENTUKAN TUNGKAI TERHADAP KEMAMPUAN SMASH SEPAK TAKRAW ATLET ARENA TAKRAW CLUB KABUPATEN KAMPAR - Risky Agustiawan; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem of this research is the ball is not sliding hard in the opponet’s area and it’s hard taken or reached by opponent players and sometimes the ball does not enter the opponet’s area or even stuck on net when the players doing ball smash. The purpose is to find out how big the relationship of leg muscle and leg flexibility at the smash ability of Arena Takraw Club Kampar Regency sepak takraw athlete. The technique in this research is using total sampling by amount to 8 Arena Takraw Club Kampar Regency atheletes. The research is using correlation technique. Then, datatest is using normality test, correlation test, product moment correlation test, and significant test α= 0.05. The normality tes variable X1, L0maks (0,179) < Ltabel (0,285), X2 L0maks (0,2221) < Ltabel(0,285) and the normality test Y, L0maks (0, 107) < Ltabel (0,285) in the other words normal data and the conclusion of this research shows there is significant relationship between the relationship of leg muscle and leg flexibility at the sepak takraw smash ability with correlation r= 0.967 where rhitung > rtabel atau 0.967 > 0,754 and the relationship is categorized as strong thereby Ha is accepted.Key Words: Relationship, Leg Muscle Power, Hubungan, Power Otot Tungkai, Leg Flexibility,Smash Ability.